PENERAPAN MEDIA SEMPOA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III SD NEGERI 1 SANGGEUE - Nasri Diana; Raudhatun Nisa (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2024)
This study aims to determine the application of abacus media in improving the learning outcomes of 3rd grade students of SD Negeri 1 Sanggeue. The research design used is the type of classroom action research (CAR). The subjects in this study were 3rd grade students, totaling 14 students consisting of 11 female students and 3 male students. Data collection in the study was carried out by observation and tests. The results of the study showed that the average individual score in cycle I was 74.92 and increased in cycle II to 87.28. Classical completeness in cycle I was 8 students with a percentage of 57.14%, and classical completeness in cycle II was 14 students with a percentage of 100%. So it can be concluded that the application of abacus media can improve student learning outcomes in 3rd grade students of SD Negeri 1 Sanggeue.